2017
DOI: 10.3389/fneur.2017.00075
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow-Derived Cell Accumulation in the Spinal Cord Is Independent of Peripheral Mobilization in a Mouse Model of Amyotrophic Lateral Sclerosis

Abstract: Bone marrow-derived cells (BMDCs) are capable of migrating across the blood–brain barrier (BBB) and accumulating in the central nervous system (CNS) when transplanted into recipients conditioned with whole-body irradiation or chemotherapy. We used the chemotherapeutic agents busulfan and treosulfan to condition recipient mice for transplantation with bone marrow (BM) cells isolated from donor mice ubiquitously expressing green fluorescent protein. We attempted to increase the accumulation of BMDCs in the CNS b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Other therapeutics, such as an antagonist of the chemokine receptor CXCR4 (Rabinovich-Nikitin et al, 2016 ) and the myelosuppressive dealkylating agent busulfan (Peake et al, 2017 ), demonstrated improved BCNSB function in ALS models. Edaravone has been previously shown to mediate BBB repair in models of ischemic stroke, in addition to its primary mechanism of action as a free radical scavenger (Miyamoto et al, 2014 ; Tóth et al, 2014 ; Watanabe et al, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…Other therapeutics, such as an antagonist of the chemokine receptor CXCR4 (Rabinovich-Nikitin et al, 2016 ) and the myelosuppressive dealkylating agent busulfan (Peake et al, 2017 ), demonstrated improved BCNSB function in ALS models. Edaravone has been previously shown to mediate BBB repair in models of ischemic stroke, in addition to its primary mechanism of action as a free radical scavenger (Miyamoto et al, 2014 ; Tóth et al, 2014 ; Watanabe et al, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…In patients with rapidly progressing ALS, monocytes in the peripheral circulation are usually in a proinflammatory state ( Zhao et al, 2017 ). Recently, peripheral monocytes have been proven to infiltrate the CNS, which is related to improved motoneuron survival in ALS, but infiltration may be limited ( Peake et al, 2017 ). In addition, monocyte-derived macrophages are activated in ALS.…”
Section: The Crosstalk From the Peripheral Immune System To The Centr...mentioning
confidence: 99%
“…BMDC blood molecular signatures vary depending on the context, as shown by flow cytometry experiments in diseases including amyotrophic lateral sclerosis, and following BMDC engraftment in the mouse brain. 51 , 52 , 53 , 54 Nevertheless, BMDCs were reported to maintain their identity once they enter the mouse brain. 52 , 55 FLT3 + cells in the blood of wild-type C57BL/6J mice were first assessed for their expression of the leukocyte markers CD45, CD115, and GR1.…”
Section: Resultsmentioning
confidence: 99%